Assessments of genetic diversity and anthracnose disease response among Zimbabwe sorghum germplasm. Issue 2 (13th January 2014) - Cuevas, Hugo E.; Prom, Louis K.; Erpelding, John E.; Brotons, Veronica; Lübberstedt, T.
Abstract The USDA‐ARS National Plant Germplasm System maintains a Zimbabwe sorghum collection of 1235 accessions from different provinces. This germplasm has not been extensively employed in US breeding programmes due to the lack of phenotypic and genetic characterization. Therefore, 68 accessions from Zimbabwe were phenotyped, and evaluated for their anthracnose response for two consecutive years, and genetically characterized with 21 simple sequence repeat markers. Phenotypic analysis showed significant differences among accessions with plant height and panicle length being the most variable traits. Likewise, 25 accessions were anthracnose resistant, nine showed variable responses and 34 were susceptible. Genetic analysis identified 174 alleles with an average of 8.3 alleles and 11.8 genotypes per locus and a polymorphic information content of 0.60. These results reflect a moderate genetically diverse germplasm. Neighbour‐joining clustering analysis revealed that the majority of anthracnose‐resistant accessions showed high genetic relatedness; therefore, this germplasm might represent one to six new sources of resistances. Results presented herein show that the Zimbabwe collection contains valuable germplasm for breeding programmes and is an important source of anthracnose resistance.